Rare case of Killian-Pallister syndrome associated with idiopathic short stature detected with fluorescent in situ hybridization on buccal smear - Sukarova-Angelovska, Elena (Mol Cytogenet, 2016)
BACKGROUND: Killian-Pallister syndrome (KPS) is a rare form of chromosomal mosaicism and is defined by the existence of an extra chromosome 12 in some cell lines in one individual. The degree of mosaicism varies among tissues and dictates the clinical presentation of the syndrome. The clinical features of Killian-Pallister syndrome include mental retardation, typical facial dysmorphism and pigmentation defects. CASE PRESENTATION: We present a rare case of Killian-Pallister syndrome with severe form of the disease associated with isolated growth hormone deficiency and low-rate mosaicism on buccal smear. The absence of a marker chromosome 12p in lymphocyte cultures and the low degree of mosaicism lead to frequent misdiagnosis of this condition. CONCLUSIONS: The selection of tissue sampling is crucial in establishing the diagnosis of Killian-Pallister syndrome. Fluorescent in situ hybridisation on buccal smear remains the golden standard as a screening method if a suspicion of the syndrome exists.